2017
DOI: 10.1037/ipp0000064
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Stress Symptoms, Forgiveness, and Meaning in Life in Four Traumatized Regions of the World

Abstract: The present study examined self-reported levels of traumatic stress symptoms, forgiveness, and meaning in life in residents of regions experiencing ongoing violence (Middle East), recent past violence (Africa), distant past violence and disaster (Caucasus), and recent natural disaster (Caribbean). The sample included 900 individuals from Africa (Kenya n = 149; Burundi n = 104; Rwanda n = 57), the Middle East (Israel n = 34; Jordan n = 22; Palestine n = 220), the Caucasus (Armenia n = 109), and the Caribbean (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In the face of traumatic experiences, including those that occur in the context of forced migration, religion and spirituality influence individual coping. Research among forced migrants (Ai, Peterson, & Huang, 2003; Benson, Sun, Hodge, & Androff, 2012; Gozdziak, 2002) as well as among other groups impacted by traumatic events (Currier, Mallot, Martinez, Sandy, & Neimeyer, 2013; Johnstone, Hanks et al, 2017; Johnstone, Yoon et al, 2012; Park et al, 2017; Stratta et al, 2013; Toussaint et al, 2017) examines relationships between religion, trauma, and coping. Mental health symptoms often result from the trauma experienced prior to forced migration as well as difficulties experienced during transit and while in countries of first asylum (Afifi et al, 2016; Berzengi, Berzenji, Kadim, Mustafa, & Jobson, 2017; Hutson et al, 2016; Thomas, Roberts, Luitel, Upadhaya, & Tol, 2011).…”
Section: Literature Review: Religion Among Forced Migrant Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of traumatic experiences, including those that occur in the context of forced migration, religion and spirituality influence individual coping. Research among forced migrants (Ai, Peterson, & Huang, 2003; Benson, Sun, Hodge, & Androff, 2012; Gozdziak, 2002) as well as among other groups impacted by traumatic events (Currier, Mallot, Martinez, Sandy, & Neimeyer, 2013; Johnstone, Hanks et al, 2017; Johnstone, Yoon et al, 2012; Park et al, 2017; Stratta et al, 2013; Toussaint et al, 2017) examines relationships between religion, trauma, and coping. Mental health symptoms often result from the trauma experienced prior to forced migration as well as difficulties experienced during transit and while in countries of first asylum (Afifi et al, 2016; Berzengi, Berzenji, Kadim, Mustafa, & Jobson, 2017; Hutson et al, 2016; Thomas, Roberts, Luitel, Upadhaya, & Tol, 2011).…”
Section: Literature Review: Religion Among Forced Migrant Womenmentioning
confidence: 99%
“…Mental health symptoms often result from the trauma experienced prior to forced migration as well as difficulties experienced during transit and while in countries of first asylum (Afifi et al, 2016; Berzengi, Berzenji, Kadim, Mustafa, & Jobson, 2017; Hutson et al, 2016; Thomas, Roberts, Luitel, Upadhaya, & Tol, 2011). Religion may facilitate coping with stress, depression, and anxiety (Koenig et al, 2012; Levin, 2010) through providing a source of meaning and easing adjustment (Gozdziak, 2002; Hipolito et al, 2014; McMichael, 2002; Raghallaigh, 2011; Toussaint et al, 2017). Some research suggests traumatic loss is associated with increases in religious coping, daily spiritual experiences, and organized religiousness (Currier et al, 2013), while other research has found trauma to be associated with a weakening of spirituality (Stratta et al, 2013).…”
Section: Literature Review: Religion Among Forced Migrant Womenmentioning
confidence: 99%
“…Offending situations abound, and exemplars would include catastrophic events such as natural disaster or terminal or chronic illness (e.g., COVID-19). It is uncanny that forgiveness has been theoretically and empirically tied to human-made and natural disasters and acts of god (Worthington Jr et al, 2016 ; Toussaint et al, 2017 ; Fincham and May, 2021 ), but consideration of forgiveness of situations and its role in resilience and recovery has been virtually absent. This is a significant omission in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Research on forgiveness in fifteen countries showed a positive relationship between forgiveness, meaning-making, and a decrease of trauma-related symptoms (Toussaint et al, 2017). Additional research revealed that meaning-making combined with forgiveness alleviates and decreases symptoms of trauma (Toussaint, Kalayjian, Diakonova-Curtis, 2017).…”
Section: Forgiveness Transforms Traumamentioning
confidence: 99%